29 Production of ultra-thin decellularised dermis to treat severe ocular diseases. (16th November 2022) - Barrera, Valentina; Joseph, Agatha; Romano, Vito; Levis, Hannah J; Hamill, Kevin; Kaye, Stephen; Rooney, Paul
Abstract : Introduction: The ocular surface may be damaged by several ocular conditions such as chemical trauma, infection, neoplasia or autoimmune disease causing a loss of tissue and function leading to a painful loss of vision. Tissue regeneration is needed to re-establish homeostasis of the ocular surface and to preserve vision. Present replacement strategies have limitations ranging from availability of the same type of tissue to long-term stability. NHSBT currently produces decellularised dermis (DCD) for clinical allografting; comprising a "thin" (up to 1.0 mm) and a thick (>1.2 mm) DCD, used to treat non-healing leg ulcers or in rotator cuff repair. Even the thin DCD, however, is too thick for ophthalmic purposes. The objective of this study was to develop a new ultra-thin DCD for ocular allografting. Materials and Methods: Skin was retrieved, with consent for non-clinical use, from the back, front and back of the thighs of 3 different deceased donors, within 48 hours post-mortem. The tissue was cut into 5x5 cm squares and decellularised over 5 days as follows: decontamination with antimicrobials, de-epidermalisation (1M NaCl), hypotonic washes, detergent washes (with 0.01% SDS) and nuclease incubation. The DCD obtained was examined for integrity, handleability, residual remaining DNA and potential ultra-structural changes (by histology, DAPI and hematoxylin and eosin staining). Results: We obtained an intact ultra-thin DCD using the same standard GMP protocol, regularly used to decellularise skin for clinical use. Tissue handleability was comparable to amniotic membrane, as evaluated by the ophthalmic surgeons as well as tissue bank assistants. The mean thickness of the tissue was 0.25 mm (±0.11) at the end of processing (total N=18 samples from 3 donors). Histology confirmed successful removal of epithelial cells and integrity of the extracellular matrix. Conclusion: We have successfully validated standard operating procedures for the production of ultra-thin DCD, in the attempt to obtain a valid alternative to amnion for the reconstruction of specific ocular regions (fornix, eye lids), where increased strength may be required. The thickness measurements at the end of processing suggest ultra-thin DCD obtained could represent a promising scaffold for regeneration of conjunctival tissue.